(untitled) (Fiep Bulletin - online, 2016)
BACKGROUND: Urinary incontinence became an issue and an increasingly common complaint in gynecology clinics. It is defined as the involuntary loss of urine through the urethra, which results in pain and can intervene in the quality of life making a big impact on the health of these women. OBJECTIVE: To assess the prevalence of urinary incontinence in women, verify the factors related to urinary incontinence and the impact on health of incontinent women. METHODS: A cross-sectional study and quantitative survey data. The survey was conducted in the city of Three Bars of Paraná (PR) with forty-six women aged 25 to 80 members of the Mothers’ Friendship Club. To meet the objective was used International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) and to complement the survey, a questionnaire was prepared by the author for the purpose of raising other data such as walking your health today, how often will the bathroom during the day, and finally gets up at night to urinate. RESULTS: Among the 46 women studied were found urinary incontinence in a total of 45.45% women and 93.46% reported that it still does not interfere with their health. CONCLUSION: There was research conducted a high prevalence of urinary incontinence among women residing in rural Three Bars of Paraná, and we observed that there was an interference with quality of life, but most participants did not consider as a matter of health.